Controlling the hydrogenolysis of silica-supported tungsten pentamethyl leads to a class of highly electron deficient partially alkylated metal hydrides. Issue 2 (8th December 2015) - Maity, Niladri; Barman, Samir; Callens, Emmanuel; Samantaray, Manoja K.; Abou-Hamad, Edy; Minenkov, Yury; D'Elia, Valerio; Hoffman, Adam S.; Widdifield, Cory M.; Cavallo, Luigi; Gates, Bruce C.; Basset, Jean-Marie
Abstract : Accessing highly electron deficient partially alkylated tungsten hydrides on silica via controlled hydrogenolysis of surface organometallic complex (Si–O–)W(Me)5 . Abstract : The well-defined single-site silica-supported tungsten complex [(Si–O–)W(Me)5 ], 1, is an excellent precatalyst for alkane metathesis. The unique structure of1 allows the synthesis of unprecedented tungsten hydrido methyl surface complexes via a controlled hydrogenolysis. Specifically, in the presence of molecular hydrogen, 1 is quickly transformed at −78 °C into a partially alkylated tungsten hydride, 4, as characterized by 1 H solid-state NMR and IR spectroscopies. Species4, upon warming to 150 °C, displays the highest catalytic activity for propane metathesis yet reported. DFT calculations using model systems support the formation of [(Si–O–)WH3 (Me)2 ], as the predominant species at −78 °C following several elementary steps of hydrogen addition (by σ-bond metathesis or α-hydrogen transfer). Rearrangement of4 occuring between −78 °C and room temperature leads to the formation of an unique methylidene tungsten hydride [(Si–O–)WH3 (CH2 )], as determined by solid-state 1 H and 13 C NMR spectroscopies and supported by DFT. Thus for the first time, a coordination sphere that incorporates both carbene and hydride functionalities has been observed.